2018
DOI: 10.1371/journal.pone.0206197
|View full text |Cite|
|
Sign up to set email alerts
|

The protective role of family structure for adolescent development in sub-Saharan Africa

Abstract: Several studies have focused on the risk factors associated with adolescent developmental outcomes, but the literature on the role of protective factors at the family and community level for positive adolescent development is scarce, especially in sub-Saharan Africa (SSA). We hypothesize that ensuring a supportive environment for adolescents may result in delayed sexual debut for adolescents in SSA. The relationship between family structure and positive adolescent sexual behaviour, measured as delay in sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…Our findings above illustrate that female adolescent who live with both parents had higher odds of delaying sexual debut, although results were not significant. Similar results were seen from a study in Africa (Somefun & Odimegwu, 2018). Many scholars hold the view that family has a strong influence on adolescent's sexual behavior.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings above illustrate that female adolescent who live with both parents had higher odds of delaying sexual debut, although results were not significant. Similar results were seen from a study in Africa (Somefun & Odimegwu, 2018). Many scholars hold the view that family has a strong influence on adolescent's sexual behavior.…”
Section: Discussionsupporting
confidence: 85%
“…Parents' engagement and communication are important to adolescents' development of sexual values and attitudes (Noller & Atkin, 2014). In addition, various studies have also shown the relation of family structure and living arrangement on delayed sexual initiation (Pilgrim et al, 2014;Somefun & Odimegwu, 2018;Stark et al, 2016;Tenkorang & Adjei, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Single parents may have more difficulty in supervising the behaviour of young adults compared to their counterparts who have two parents. It has been documented both in developed [51–53] and developing settings [54, 55] that young adults raised in single-parent households are more likely to exhibit adverse behavioural outcomes. The mechanism through which this occurs could be through the support and parental interaction that could be available in a two-parent household.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…However, the practice of protective sexual behaviours and its determinants among this cohort has received little attention. A review of the literature shows that family structure (that is, living with single or both parents or none of them) is associated with the sexual behaviour of young people [1618]. Other family-related factors like parent-adolescent sexual communication [1921], parent-child co-residence instability [22] and socio-economic background [23] have been found to also influence the sexual behaviours of young people.…”
Section: Introductionmentioning
confidence: 99%